Elective versus Emergency Cesarean Sections : Mother and Fetal Outcome: Luaran Ibu dan Bayi pada Operasi Sesar Elektif dan Emergensi - Christofer J. H. Ladja; IMS Murah Mano; Andi M. Tahir; St. Maisuri T. Chalid (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objective: To compare the outcomes of mothers and newborns in emergency cesarean section and elective cesarean section.Methods: A prospective cohort study included 120 pregnant women consists of 60 women who performed an emergency cesarean section and 60 women who underwent elective cesarean section. Age, education level, occupation, income, history of comorbidities, history of abortion or miscarriage, antenatal care history, decision-making time until surgery is performed along with other components required, duration of operation, outcome of mother and fetal were obtained through interviews and questionnaires. Data were analyzed regarding fetal outcome and cesarean sections indications.Results: The maternal and fetal outcome between emergency and elective cesarean section were not significantly different regarding on hospital stay, dehiscence, NICU admission, Apgar score and newborn status (dead or alive). Blood transfusion is the main difference signifi cant indication for maternal outcome between emergency and elective procedure (p less than 0.05). The total duration of procedure less than 60 or more than 60 minutes and maternal-fetal outcome not signifi cantly different between two type of procedures.Conclusions: Emergency cesarean section at preterm gestational age with an operating time less than equal to 60 minutes leads to greater transfusion blood requirements compared with elective cesarean section.Keywords: emergency cesarean section, elective cesareansection, mother-infant outcome. AbstrakTujuan: Membandingkan luaran ibu dan bayi baru lahir di seksio sesarea emergensi dan elektif.Metode: Penelitian kohort prospektif melibatkan 120 perempuan hamil terdiri atas 60 perempuan yang melakukan operasi seksio sesarea emergensi dan 60 perempuan melakukan operasi elektif. Usia, tingkatpendidikan, pekerjaan, pendapatan, riwayat komorbiditas, riwayat aborsi atau keguguran, riwayat asuhan antenatal, waktu pengambilan keputusan sampai operasi dilakukan bersamaan dengan komponen lain yang diperlukan, lamanya operasi, luaran ibu dan bayi diperoleh melalui wawancara dan kuesioner. Data yang dianalisis mengenai luaran ibu dan bayinya.Hasil: Luaran ibu dan bayi antara seksio sesarea emergensi dan elektif tidak berbeda bermakna dalam hal lama rawat inap, dehisensi, admisi, skor Apgar dan status bayi baru lahir (meninggal atau hidup). Transfusi darah adalah indikasi penting utama yang berbeda untuk luaran ibu antara prosedur emergensi dan elektif (p kurang dari 0,05). Durasi total prosedur kurang dari 60 atau lebih dari 60 menit dan luaran ibu tidak berbeda secara signifikan antara kedua jenis seksio sesarea.Kesimpulan: Tindakan seksio sesarea emergensi pada usia gestasi prematur dengan waktu operasi kurang dari sama dengan 60 menit menyebabkan kebutuhan transfusi darah lebih besar dibandingkan seksio sesarea elektif.Kata kunci: luaran ibu-bayi, seksio sesarea elektif, seksio sesarea emergensi.